Review on the protective mechanism of astragaloside IV against cardiovascular diseases - Yang, Chunkun; Pan, Qingquan; Ji, Kui; Tian, Zhuang; Zhou, Hongyuan; Li, Shuanghong; Luo, Chuanchao; Li, Jun (Frontiers in Pharmacology, 2023)
Cardiovascular disease is a global health problem. Astragaloside IV(AS-IV) is a saponin compound extracted from the root of the Chinese herb Astragalus. AS-IV has been shown to have a variety of pharmacological properties over the past few decades. It can protect myocardium through anti-oxidative stress, anti-inflammatory, regulation of calcium homeostasis, improvement of myocardial energy metabolism, anti-apoptosis, anti-cardiomyocyte hypertrophy, anti-myocardial fibrosis, regulation of myocardial autophagy, improvement of myocardial microcirculation and other ways. AS-IV has certain protective effects on blood vessels. For example, it can protect vascular endothelial cells through anti-oxidative stress and anti-inflammatory pathways, relax blood vessels, stabilize atherosclerotic plaques, and inhibit the proliferation and migration of vascular smooth muscle cells. The bioavailability of AS-IV was low. Toxicology indicates that AS-IV is safe, but should be used with caution in pregnant women. In this paper, we review the mechanism of AS-IV prevention and treatment of cardiovascular diseases in recent years, with a view to providing reference for future research and drug development.